Gestão da permanência de acadêmicas em cursos de formação docente: uma questão de gênero - Venturini, Sandra Mara (2017)
The nocturn licensing courses of the Centre of Education of the Federal University of Santa Maria (UFSM) are academic formation courses aiming to increase the higher education’s admission, as well as ensuring its quality. In this context, understanding the academic achievement process and the evasion causes, from a gender perspective, could help on the permanence management of the college students of these licentiate programs. The research problem is “The gender questions, connected to the sexual division of labour, interfere in the academic achievement process, permanence or evasion of the academics of the nocturn licensing courses of the Centre of Education of UFSM”? The project is inserted on the Research Line of Pedagogical Administration and Educational Context (LP2), of the course of Professional Masters on Public Politics and Educational Management of Centre of Education of UFSM. It boards the delicate evasion matter e the low academic achievement from the concepts connected to gender subjects, such as the idea of “patriarchy” by Heleieth Saffioti (2004), Patrícia Rocha (2009), Michelle Perot (2016) and Mary Wollstonecraft (2016), the “sexual division of labour”, by Acelí de Assis Magalhães (2001), “ways to eternize subordination” by Pierre Bourdieu (2002), among others. The research theme arises from some restlessness delineated along my path, especially on professional field, which take me to a reflection about the need to study and consider the influence and the effects that the gender matters, particularly the ones connected to the sexual division of labour, produce on the academic life of the college students of the noturn licensing course of the Centre of Education of UFSM. The profiles of such academics, mostly have some particularities: they are mothers and wives, that perform concomitantly roles on paid labour, on domestic labour and that are on undergraduate programs. The methodology used on this research is qualitative, of the case study type, anchored on Lankshear and Knobel (2008), among others, from which it was possible to relate the theme with the main goals of the professional masters program. The data production was accomplished by in-depth semistructured interviews, aiming to understand the phenomenon through a qualitative analysis. The product consists on a research report “Management of Welcoming Permanence” containing this study results, which will be forwarded to the coordination of undergraduate courses, in order to point out actions and strategies that could contribute to a democratic administration focused on the academics in the undergraduate courses in question.